Respuesta :
Answer:
[tex]x=3\log_3 (2) +8[/tex]
Step-by-step explanation:
Here we are using power rule first.
Power rule = The logarithm of an exponential number is the exponent times the logarithm of the base [tex][log(a)^{b}=b\times log(a)][/tex].
For the function given.
[tex]3^{(x-8)} = 8[/tex],using log function both sides.
[tex](x-8)log(3)=log(8)[/tex]
Now,
[tex](x-8)=\frac{log(8)}{log(3)}[/tex]
Adding [tex]8[/tex] both sides.
[tex]x=\frac{log(8)}{log(2)} +8[/tex]
And we know that [tex]8=2^{3}[/tex] so we can further write [tex]log(8)=log(2^{3})=3log(2)[/tex]
Then we have [tex]x=\frac{3\log(2)}{\log 3} +8[/tex].
Now, using change of base formula:
[tex]\frac{\log y}{\log b}=\log_b y[/tex]
So, [tex]\frac{\log 2}{\log 3}=\log_3 2[/tex]
Our final answer is [tex]x=3\log_3 (2) +8[/tex].
Answer:
x = 3 (Log 2 base 3) + 8
Step-by-step explanation:
3^(x - 8) = 8
Take the log of both side
Log 3^(x - 8) = Log 8
Recall:
log a^b = b log a
Log 3^(x - 8) = Log 8
(x - 8) Log 3 = Log 8
Divide both side by log 3
x - 8 = Log 8 / log 3
Recall:
8 = 2^3
x - 8 = Log 8 / log 3
x - 8 = Log 2^3 / log 3
x - 8 = 3 Log 2 / log 3
Recall:
logb y = log y / log b
log y / log b = logb y
x - 8 = 3 Log 2 / log 3
x - 8 = 3 Log3 2
Add 8 to both side
x = 3 Log3 2 + 8
x = 3 (Log 2 base 3) + 8